Lysathia flavipes and Lysathia cilliersae Cabrera sp. nov. (Coleoptera, Chrysomelidae): genetic and morphological unravelling of biocontrol agents for two invasive aquatic plants - Faltlhauser, Ana Claudia (2025)
In the search for specific natural enemies to control two invasive aquatic plants (IAP) from South America, Ludwigia grandiflora subsp. hexapetala (Onagraceae) and Myriophyllum aquaticum Haloragaceae), taxonomic challenges associated with two Lysathia Bechyné, 1959 (Chrysomelidae; Alticini) species had to be resolved. Lysathia flavipes (Boheman, 1859) exhibits significant morphological variation, causes heavy damage to both IAPs, and may represent more than one species due to the phylogenetic gap between hosts. Additionally, an undescribed Lysathia species (previously published as Lysathia sp.), sourced from Brazil, has been successfully used as a control agent for M. aquaticum in South Africa since 1994. An integrative taxonomic approach combining genetic and morphological analyses was employed. A lectotype and paralectotypesfor Graptodera flavipes Boheman, 1859 are here designated. Phylogenetic studies revealed that L. flavipes had greater genetic and morphological variation than originally described, and no evidence suggested that L. flavipes represented a species complex associated with its host plants. As a result, the species description was expanded. On the other hand, genetic and morphological differences such as body size, colouration, and genital structures further supported the description of Lysathia cilliersae Cabrera, sp. nov. and its differentiation from other closely related species, including L. flavipes and L. ludoviciana (Fall, 1910). Specimens of L. cilliersae sp. nov. collected in Misiones, Argentina, matched those from South Africa. Genetic sequences correlated with morphological vouchers, images, and illustrations of morphology and genitalia, as wellas new distribution records, are provided. This research contributes to the taxonomicknowledge of the Lysathia genus and supports accurate species identification in appliedentomological contexts, such as biological control programmes.